2021
DOI: 10.1007/s13178-021-00536-3
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Sexual Abuse in a Culturally Conservative Nigerian Society: Female Victims’ Narratives of Psychosocial Costs

Abstract: Background In the last few years, many countries have introduced laws combating image-based sexual abuse (IBSA), colloquially known as "revenge pornography." However, the significant growth in the body of literature on the legal perspectives on IBSA, and the media coverage of high profile cases have not been equally met with appreciable victimization studies. Meanwhile, the need for a victim-centered approach in studying IBSA in Nigeria is underscored by the pervasiveness and normalization of sexual violence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 25 publications
2
37
0
Order By: Relevance
“…This study found that extortion, naivety of male adults on use of communication technology; black mail and revenge were the reasons for posting of non-consensual nudities of male adults in Zambia. These findings are supported to a greater extent by the evidence collected from a study by Aborisade (2021) in which it was found that perpetrators of nonconsensual dissemination of pornographic materials depicting other individuals did so to extort victims for personal gain, to damage the victim"s personality for public disrepute or for relationship retribution (Aborisade 2021:10). The study also found that victims of non-consensual pornography suffered social shaming, social stigma, ridicule, rejection and desertion, loss of respect and dignity.…”
Section: Discussionmentioning
confidence: 91%
“…This study found that extortion, naivety of male adults on use of communication technology; black mail and revenge were the reasons for posting of non-consensual nudities of male adults in Zambia. These findings are supported to a greater extent by the evidence collected from a study by Aborisade (2021) in which it was found that perpetrators of nonconsensual dissemination of pornographic materials depicting other individuals did so to extort victims for personal gain, to damage the victim"s personality for public disrepute or for relationship retribution (Aborisade 2021:10). The study also found that victims of non-consensual pornography suffered social shaming, social stigma, ridicule, rejection and desertion, loss of respect and dignity.…”
Section: Discussionmentioning
confidence: 91%
“…Of these articles, two investigated both the non-consensual dissemination of intimate images and the threat to share intimate materials (Bates, 2017 ; Campbell et al, 2020 ), one study investigated the first two dimensions of the IBSA continuum (i.e. non-consensual taking or non-consensual sharing of intimate material) within the macro-category of TFSV (Technology-Facilitated Sexual Violence) (Henry et al, 2021 ) and two focused on the entire continuum of IBSA (Aborisade, 2021 ; McGlynn et al, 2021 ). Among these, three articles used semi-structured interviews (Aborisade, 2021 ; Bates, 2017 ; Campbell et al, 2020 ) while two studies used unstructured interviews (Henry et al, 2021 ; McGlynn et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…non-consensual taking or non-consensual sharing of intimate material) within the macro-category of TFSV (Technology-Facilitated Sexual Violence) (Henry et al, 2021 ) and two focused on the entire continuum of IBSA (Aborisade, 2021 ; McGlynn et al, 2021 ). Among these, three articles used semi-structured interviews (Aborisade, 2021 ; Bates, 2017 ; Campbell et al, 2020 ) while two studies used unstructured interviews (Henry et al, 2021 ; McGlynn et al, 2021 ). Only one article followed a mixed-method approach (Champion et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been few qualitative studies with victim-survivors of imagebased sexual abuse (see Aborisade, 2021;Bates, 2017;Henry et al, 2021a;Mandau, 2021;McGlynn et al, 2021), or with victim-survivors of technology-facilitated abuse more broadly (see Cuomo & Dolci, 2021;Douglas et al, 2019;Henry et al, 2021b;Leitão, 2021). There are even fewer qualitative studies focusing exclusively or comprehensively on victim-survivor experiences of image-based sexual abuse in the context of intimate partner abuse.…”
Section: Image-based Sexual Abusementioning
confidence: 99%